Responsibility Of The National Land Agency Of Gorontalo City For The Cancellation Of Land Certificates - magfirah - nupuri (Estudiante Law Journal, 2019)
This research aims to find out the responsibility of  the Gorontalo City National Land Agency for cancelingits land certificates. The methods used in this studyare empirical legalresearch by conducting sample withdrawal using purposive sampling and data analysis using qualitative or descriptive research approaches. The results showed that civil liability by the  Gorontalo City  National Land Agency against the certificates that were legalized by the Gorontalo State Administrative Court,  was carried out by the Gorontalo City BPN by implementing the decision of the State Administrative Court both the first level, appeal, to the cassation that had been  inkrah.  , and issue a Decree (SK) cancellation of land rights certificates. In the implementation of the duties on land certificates declared void by the State Administrative Court, the Gorontalo City National Land Agency must prepare all potential and resources, and need to conduct an analysis to carry out the verdict as a form of its responsibility for land rights certificates that are declared void, without having to be requested by the applicant back to the Gorontalo City BPN.